Blind Computation in AI Machine Operation: A Study of Homomorphic Encryption, Secure Multi-Party Computation, and Federated Learning - Owunna, Ikechukwu; Ekanem, Imoh; Ikpe, Aniekan (Annals of Optimization With Applications, 2025)
This study critically examines the emerging field of Blind Computation (BC) in Artificial Intelligence (AI) machine operations, challenging conventional approaches to data privacy and security in artificial intelligence systems. As AI continues to permeate various sectors, from healthcare to finance, the need for robust privacy-preserving techniques has become paramount.  BC  offers a promising solution by enabling AI models to process encrypted data without decryption, thus maintaining data confidentiality throughout the computational pipeline. The study explored conventional techniques in Homomorphic Encryption (HE), Secure Multi-Party Computation (SMPC), and Federated Learning (FL), presenting a comprehensive framework for implementing  BC  in AI systems. We propose novel architectures that significantly enhance data protection without compromising computational efficiency. The analysis revealed that while  BC  techniques offer unprecedented levels of privacy, they also introduce new challenges in terms of computational overhead and model accuracy. Empirical evidence demonstrating the trade-offs between privacy, performance, and precision, and propose innovative strategies to optimize these competing factors. Furthermore, we critically assess the ethical implications of  BC , examining its potential to either mitigate or exacerbate existing biases in AI systems. This study was concluded by outlining a roadmap for future research, emphasizing the need for interdisciplinary collaboration to address the technical, ethical, and regulatory challenges associated with  BC  in AI. The findings obtained have significant implications on the design and deployment of privacy-preserving AI systems across various domains, potentially revolutionizing the way sensitive data is processed in the age of artificial intelligence.